Petrography and chemical composition of the lava flows at DSDP Leg 55 Holes - Avdeiko, G P; Khubunaja, S A; Vande-Kirkov, J V (Supplement to: Avdeiko, GP et al. (1980): Petrography and chemical composition of the lava flows from the Emperor Seamounts, DSDP Leg 55. In: Jackson, ED; Koisumi, I; et al., (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 55, 571-584, https://doi.org/10.2973/dsdp.proc.55.122.1980, 1980)
During DSDP Leg 55, volcanic rocks were recovered at Sites 430, 432, and 433, on Ojin, Nintoku, and Suiko seamounts, respectively, in the Emperor Seamount chain. Of the five lava flows recovered at Hole 430A, the upper four flows are typical hawaiites and the lowest flow is tholeiite. Three lava flows of alkalic basalts recovered at Hole 432A on Nintoku Seamount are petrographically and chemically similar to the analogous rocks from the Hawaiian Islands. Ninety-six cooling units, from 163 to 550 meters sub-bottom, were sampled at the re-entry Hole 433C. Most of them are lava flows and others are secondary thin flows or flow lobes from fissures of basic flows. The three uppermost flows are alkalic basalts. Eight individual cooling units of picritebasalts (Flow Units 4A-4H) occur below them. The underlying sequence of flows is composed almost entirely of tholeiites; only four flows are transitional toward alkalic basalts, and one of them is picrite-basalt.